High birthweight and shoulder dystocia: the strongest risk factors for obstetrical brachial plexus palsy in a Swedish population-based study. - Mollberg, M; Hagberg, H; Bager, B; Lilja, H; Ladfors, L (2005)
BACKGROUND: Obstetrical brachial plexus palsy (OBPP) is a serious form of neonatal morbidity. OBJECTIVE: The aim of this work was to study the incidence of OBPP and to analyze its risk factors. METHODS: This is a population-based retrospective case-control study. All deliveries recorded in the Swedish Medical Birth Registry between 1987 and 1997 (n = 1 213 987) were investigated. Cases (n = 2399) with OBPP were compared to all other cases. RESULTS: The incidence of OBPP increased from 0.17 in 1987 to 0.27% in 1997 (p = 0.002). During the same time period, the mean birthweight increased from 3483 to 3525 g. Birthweight increasing from 4000 g was associated with a progressive rise in OBPP risk. Other significant risk factors associated with the injury were shoulder dystocia, breech presentation in vaginal delivery, operative vaginal delivery, diabetes mellitus, induction of labor, protracted active phase, secondary arrest of dilatation, and epidural anesthesia. Cesarean section was associated with a decreased risk of OBPP. If 5000 g is chosen as cut-off for cesarean section, 85% of the infants in this weight class are underestimated using ultrasonography. Approximately, 331 abdominal deliveries have to be performed to avoid one case of OBPP. CONCLUSIONS: Shoulder dystocia and infant birthweight of 4500 g and more are the strongest risk factors for OBPP in a Swedish population.